Age Characteristics of Patients With Type 2 Diabetic Foot Ulcers and Predictive Risk Factors for Lower Limb Amputation: A Population-Based Retrospective Study - Yuanying Yao; Lei Chen; Yu Qian (Journal of Diabetes Research)
Conclusion: Most patients with DFU were in the age group of 50–59 years, but the majority of deaths occurred in the 70–79-year age group. Several factors influence the amputation, and those findings provide new insights into the relationship between the severity of narrowed blood vessels and the likelihood of amputation.